UPAYA MENINGKATKAN KINERJA GURU DALAM PENGEMBANGAN EVALUASI HASIL BELAJAR MELALUI SUPERVISI AKADEMIK KEPALA MADRASAH - Agus Kosasih (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
Teacher performance in developing learning outcomes evaluation is not optimal. This requires coaching by the head of the madrasah and madrasah supervisors. The form of coaching through academic supervision by the head of the madrasah towards teacher performance in developing the evaluation of learning outcomes through School Action Research is assumed to be an alternative to optimizing teacher performance. This research is a School Action Research (PTS) that was conducted in two cycles. Each cycle consists of two meetings. Each meeting consists of a number of activities which include: planning, acting, observing, and reflecting. The subjects in this study were teachers of MTs Negeri 4 West Bandung with a sample of 20 teachers. The results of the study concluded that: (1) there is a significant increase in teacher performance in the development of evaluation of learning outcomes through academic supervision, which is 64.50% in cycle I to 75.50% in cycle II, (2) teacher activities in coaching were categorized as good in every aspect, (3) improving teacher performance through academic supervision by the Head of Madrasah shows an increase at the end of the cycle, and (4) Coaching activities through academic supervision by the Head of Madrasah can help teachers improve their performance in developing learning outcomes evaluation.